Mineralogical characterization of scalings formed in geothermal sites in the Upper Rhine Graben before and after the application of sulfate inhibitors. (January 2018) - Haas-Nüesch, Ruth; Heberling, Frank; Schild, Dieter; Rothe, Jörg; Dardenne, Kathy; Jähnichen, Sabine; Eiche, Elisabeth; Marquardt, Christian; Metz, Volker; Schäfer, Thorsten
Abstract: Scale formation processes in the surface installations of geothermal power plants may have a negative effect on power plant performance. In addition, scales formed within the geothermal water circuit frequently accumulate natural radionuclides. Consequently, scale formation may lead to radiation dose rates, which are of radiological concern, and deposits, which may have to be disposed as radioactive waste. In order to minimize these problems and to foster geothermal power plant availability, it is of major interest to understand scale formation processes and to develop methods for their inhibition. One important pre-requisite towards this goal is a sound mineralogical and geochemical characterization of the formed material. Geothermal brines at sites in the Upper Rhine Graben are in general highly mineralized and become, upon cooling in the heat exchanger, supersaturated with respect to sulfate solid-solutions, e.g. (Ba, Sr)SO4, and other mineral phases. Some geothermal power plants very successfully tested the application of sulfate scaling inhibitors. Here we present mineralogical analyses of scale samples from geothermal power plants in the Upper Rhine Valley deposited in absence and presence of sulfate scaling inhibitors. Solid samples are investigated using wet-chemistry (after digestion), XRPD, SEM-EDX, XPS, EA-IRMS, Raman spectroscopy, and XANES (for explanation of abbreviations, see main text). Samples of scales deposited in the absence of a sulfate scaling inhibitor mainly consist of two phases. The largest part is made up of a barite type (Ba, Sr, Ca)SO4 solid-solution. Traces of Ra occurring in the scaling are assumed to be incorporated in the barite type solid solution. Further minor phases are sulfide phases, either an X-ray amorphous nano-particulate phase or galena (PbS). Since the application of the sulfate inhibitor, sulfate minerals are no longer detectable in the scale samples. Subsequent scalings are Pb-dominated and consist mainly of galena (PbS), elemental lead (Pb), arsenic (As) and antimony (Sb). As and Sb are likely present as a nanocrystalline intermetallic mixed compound ((Sb, As) or Pb3 (Sb, As)2 S3 ). The absence of barite-type minerals demonstrates the success of the application of the sulfate inhibitor. The precipitation of elemental Pb, As, and Sb, which are more noble than iron, may enhance the corrosion of mild steel pipes in the geothermal water circuit. Elution tests and oxidation of the scalings upon storage at atmospheric conditions demonstrate that proper disposal of the toxic heavy metal and metalloid containing scalings may be challenging.